Virtual Touch Screen Using Microsoft Kinect (International Journal of Engineering and Computer Science, 2014)
Virtual Touch Screen using Microsoft Kinect is a depth-sensing and projection system that enables interactive touch applications on everyday planar surfaces. It provides capabilities similar to that of a mouse or touchscreen. Touch screen surfaces are becoming prevalent, since they are capable of detecting the user’s actual touch points that is the points of contact on the surface. Our project presents a practical solution to achieve touch on any planar surface based on mounting a single commodity depth camera that is a Microsoft Kinect above a horizontal surface and using a projector for projection purpose. This will enable us to detect when the surface is being touched. Using Microsoft Kinect to detect touch has significant advantages: firstly, the interactive surface should not be instrumented. Secondly it is more accurate and cost effective.